Respuesta :

caylus

Answer:

Step-by-step explanation:

4) You just have to find the lcm of the denominators

a) lcm(4,3,6)=4*3=12

[tex]\dfrac{3}{4} x-\dfrac{2}{3} =\dfrac{1}{6}x\\\\12*(\dfrac{3}{4} x-\dfrac{2}{3}) =12*(\dfrac{1}{6}x)\\\\12*\dfrac{3}{4} x-12*\dfrac{2}{3} =12*\dfrac{1}{6}x\\\\9*x-8 =2*x\\\\9*x-2*x =8\\\\7*x=8\\\\x=\dfrac{8}{7} \\[/tex]

b) I don't know the name of the property but it is :

"We can multiply the two members of an equality by the same non-zero number, we obtain an equality. "

5)

[tex]-6x+10+8x=12-4x\\\\(-6x+10)+8x=12-4x\\\\8x+(-6x+10)=12-4x\\\\8x-6x+10=12-4x\\\\2x+10=12-4x\\....[/tex]